IMPLEMENTASI PRODUK TABUNGAN UMUM SYARIAH DI KJKS BMT UGT SIDOGIRI CABANG PEMBANTU TLANAKAN PAMEKASAN - Syafi'i Syafi'i; Fadllan Fadllan (Institut Agama Islam Negeri Madura, 2015)
These shari’ah public savings products is entrusted (wadiah) which in principle is pure deposits of from party saving or entrusting to the person receiving the deposit o be used or not used in accordance with the provisions. Safekeeping must be kept and maintained by the party that receives deposits, and this deposit can be taken at any time when required by the party who left it. The focus of this research are: 1) How does the products management of Shari’ah Public savings (Wadiah) at Shari’ah Financial Service Cooperative of Baitul Maal Wat Tamwil Enterprises Joint Integrated Sidogiri of the Helper Branch Tlanakan Pamekasan. 2) How is the implementation of Shari’ah public savings (Wadiah) at Shari’ah Financial Service Cooperative Baitul Maal Wat Tamwil Enterprises Joint Integrated Sidogiri of the Helper Branch Tlanakan Pamekasan in the perspective of economic law of shari’ah. This research used a qualitative approach, this research used by some measures. First, adjust the qualitative methods more easily when faced with a double reality. second, this method presents the direct nature of the relationship between researchers and informants. Third, this method is more sensitive and can adjust to the research setting and able to do the sharpening of the patterns of values encountered. The result of this research is a contract of Mudharabah Musytarakah in KJKS BMT UGT Sidogiri of Helper Branch Tlanakan Pamekasan indeed most are in accordance with the Shari’ah banking system, but there is a small part that deviated from the Shari’ah banking system and Legal Aspects BMT lies on the source transparency for the results received by the Client savings and distribution transparency of funds all savers.